2007
DOI: 10.1016/j.ecolecon.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the immeasurable — A survey of sustainability indices

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
219
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 698 publications
(264 citation statements)
references
References 15 publications
1
219
0
12
Order By: Relevance
“…Além disso, a avaliação da sustentabilidade tem o propósito de comunicar aos stakeholders os esforços e o progresso de uma organização nas dimensões econômica, ambiental e social (Böhringer & Jochem, 2007;Lozano, 2006;Ness et al, 2007;Singh et al, 2009;Wilson et al, 2007).…”
Section: Avaliação Da Sustentabilidadeunclassified
See 2 more Smart Citations
“…Além disso, a avaliação da sustentabilidade tem o propósito de comunicar aos stakeholders os esforços e o progresso de uma organização nas dimensões econômica, ambiental e social (Böhringer & Jochem, 2007;Lozano, 2006;Ness et al, 2007;Singh et al, 2009;Wilson et al, 2007).…”
Section: Avaliação Da Sustentabilidadeunclassified
“…Böhringer & Jochem (2007) corroboram essas afirmações, dizendo que atualmente há um forte interesse na avaliação da prosperidade econômica, da qualidade ambiental e da coerência social.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…But it has been shown that many internationally publicized composite sustainability indicators neglect basic scientific rules for the selection of input variables, normalization and weighting of these variables and also formal conditions for meaningful aggregation (Böhringer and Jochem, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability is notorious as an extremely poorly defined and operationalized concept (Böhringer and Jochem 2007, Wilson et al 2007, Davidson 2010, Mori and Christodoulou 2012. For example, differing measures of national sustainability have placed the same nation in the top five in the world on one metric while in the bottom five in the world on a different metric (Wilson et al 2007).…”
Section: Sustainabilitymentioning
confidence: 99%